The Cultural Roots of Firm Entry, Exit, and Growth - Katharina Erhardt; Simon Haenni (Center for Economic Studies and ifo Institute (CESifo), 2021)
Can culture explain persistent differences in economic activity among individuals and across regions? A novel measure of cultural origin enables us to contrast the entrepreneurial activity of individuals located in the same municipality but whose ancestors lived just on opposite sides of the Swiss language border in the 18th century. Individuals with ancestry from the German-speaking side create 20% more firms than those with ancestry from the French-speaking side. These differences persist over generations and independent of the predominant culture at the current location. Yet, founders' ancestry does not affect exit or growth of newly-founded firms. A model of entrepreneurial choice and complementary survey evidence suggest that the empirical patterns are mainly explained by differences in preferences, rather than skill. The results have sizable economic implications, accounting for 120,000 additional jobs over a period of 15 years.
Keywords: D22; L26; O12; Z10; 330; culture; entrepreneurship; natural experiment; spatial RDD